Material Analysis of Damaged Breech Locking Element of Machine Gun - Kusmic, David; Studeny, Zbynek; Svoboda, Emil (Manufacturing Technology Journal, 2015)
Weapons are special systems, which have high demand in terms of reliability, safety and durability especially in the case of automatic weapons. The most stressed parts of weapons are barrels, breech, locking elements etc. This paper si focused on the failure of locking element, which is used for set the breech baffle and for locking of the breech. From the structural point of view the locking element is highly dynamically stressed component. During the shooting cycles are the shocks transferred into these components, therefore specified material requirements of the locking element are needed. The material of locking element must be modified to hard surface with tough core with thickness corresponding to the size and frequency of shocks to prevent the fatigue failure. The manufacturing documentation wasn't available, therefore the chemical analysis was performed using the GDOES/Bulk method. The results were compared with material standards to determine the Czech steel equivalent. The damaged locking element was metallographically tested, the surface and microhardness testing was performed by Vickers method. The fracture surface morphology was using the light and electron microscopy (SEM) observed.
Keywords: Locking element; material analysis; failure